2010
DOI: 10.1016/j.epsl.2010.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum isotope behaviour accompanying weathering and riverine transport in a basaltic terrain

Abstract: Editor: M.L. DelaneyKeywords: molybdenum (Mo) isotopes basaltic weathering riverine inputs estuarine mixingThe application of the molybdenum (Mo) isotope system as a proxy for determining changes in the redox state of the oceans is predicated on the assumption that the composition of continental input can be characterised from crustal rock types, and remains constant. However, it has recently been shown that the δ 98/95 Mo composition of global rivers varies between 0.15‰ and 2.4‰ and is therefore systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 43 publications
(79 reference statements)
8
95
1
Order By: Relevance
“…Non-conservative signatures have actually been observed for dissolved Mo concentrations in estuarine and coastal waters (Dellwig et al, 2007;Rahaman et al, 2010) and in the eastern tropical Pacific (Tuit and Ravizza, 2003). The non-conservative signatures also reported for δ 98/ 95 Mo in the low salinity zone of an estuary (Pearce et al, 2010a). Possible mechanisms for non-conservative behavior of dissolved Mo in oxic seawater are uptake by phytoplankton and cyanobacteria, remineralization from biogenic particles, adsorption to Mn-Fe (oxyhydr)oxides, and reductive release from Mn-Fe (oxyhydr)oxides.…”
Section: Homogeneity Of Mo Isotopes In the Modern Oxic Oceanmentioning
confidence: 64%
See 2 more Smart Citations
“…Non-conservative signatures have actually been observed for dissolved Mo concentrations in estuarine and coastal waters (Dellwig et al, 2007;Rahaman et al, 2010) and in the eastern tropical Pacific (Tuit and Ravizza, 2003). The non-conservative signatures also reported for δ 98/ 95 Mo in the low salinity zone of an estuary (Pearce et al, 2010a). Possible mechanisms for non-conservative behavior of dissolved Mo in oxic seawater are uptake by phytoplankton and cyanobacteria, remineralization from biogenic particles, adsorption to Mn-Fe (oxyhydr)oxides, and reductive release from Mn-Fe (oxyhydr)oxides.…”
Section: Homogeneity Of Mo Isotopes In the Modern Oxic Oceanmentioning
confidence: 64%
“…Although pioneering studies assumed that the Mo input from rivers to the ocean would have a Mo isotopic composition similar to continental rocks (δ 98/95 Mo ~ 0‰; Siebert et al, 2003), recent studies on river and estuarine water revealed great variations in the isotopic composition of dissolved Mo (δ 98/95 Mo = -0.1 to 2.3‰; Archer and Vance, 2008;Pearce et al, 2010a;Scheiderich et al, 2010;Neubert et al, 2011). Data on the hydrothermal input are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The W/Ta ratio vs. depth in the Chhindwara profile is illustrated in Figure 4a For instance, at present, it is known that river waters are variably enriched in the heavier isotopes of Mo relative to igneous rocks and at least some of this fractionation is caused by preferential retention of lighter Mo isotopes in soils, in tandem with catchment geology variation and riverine Mo removal (Archer and Vance, 2008;Pearce et al, 2010;Neubert et al, 2011;Voegelin et al, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Today, seawater carries a homogeneous isotope composition of δ 98 Mo = 2.3±0.1‰ [4][5][6] relative to the oceanic input of dissolved Mo in rivers (90%) at ~0.7‰ [7][8][9]) with the rest from low temperature hydrothermal fluids [10] at ~0.8‰ [11].…”
Section: A1: Modern Mo Cyclementioning
confidence: 99%